PENGARUH IMPLEMENTASI SPECIAL ECONOMIC ZONE BATAM BINTAN KARIMUN TERHADAP PENINGKATAN INDUSTRI PARIWISATA DI KABUPATEN BINTAN PADA TAHUN 2012-2014 - Gita Indira Puspita; Faisyal Rani (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2016)
The research present describe the influence of implementation Special Economic Zone in Batam Bintan Karimun towards increase of tourism industry in Bintan Regency in 2012-2014. Special economic zone are dealed in 2007, before implementation special economic zone, Batam are the teritory that implemented of free trade zone. Implementation of special economic zone have purpose to increase a economic growth in teritory border especially for Batam Bintan Karimun.The research use the methode are qualitative methodes that analyze problem research by describe the subject and object conditions based on real fact. This research use location in Bintan Regency and researcher collect data from books, government regulation, journal, mass media, website. This research use neo liberalism perspective with the concept of tourism.The conclusion of this research are influence of implementation Special Economic Zone in Batam Bintan Karimun towards tourism in Bintan Regency are increase of transprotation in Bintan such as road, bridge and airport, and increase of investations value and international tourism event in integrated tourism Lagoi area likes Bintan Triathlon, Tour de Bintan, Fishing Festival and Bintan Mountain Trecking and Durian Party.Keywords: influence, implementation, special economic and tourism.